EFFECT OF GLYCEROL ON MILK YIELD, ITS QUALITY AND BLOOD PARAMETERS OF HOLSTEIN COWS - W.A. Khalid,; N.N. Al-Anbari, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The aim of this study was to investigate the effect of adding glycerol at different levels (T1 = control treatment without glycerol, T2 = 75 ml and T3 = 150 ml glycerol) on daily milk yield, milk components and some blood parameters of Holstein cows during the period of 60 days. Milk yield increased significantly (P≤0.05) at 15th day of the experiment, and highly significant (P≤0.01) at 30th and 60th days of the experiment in T3 group. Percentage of milk protein and lactose increased (P≤0.01) in T2 and T3 groups and the percentage of milk fat in the T3 group decreased at day 60 of the experiment. The blood glucose concentration increased (P≤0.01) in T2 and T3 groups at 30 and 60 days of the experiment. Triglyceride concentration increased (P≤0.01) in the blood of T2 and T3 treated cows at day 60. The concentration of cholesterol, NEFA and BHBA decreased (P≤0.01) in T3 treated cows at day 60 of the experiment. The concentration of phosphorous and magnesium were also affected as a result of glycerol treatment. It can be concluded that the addition of dietary glycerol 150 ml / day enhanced milk yield, protein and lactose percentage, and improved blood parameters by increasing blood glucose and reducing NEFA and BHBA concentrations of Holstein cows.